TEKWAN (TEKNOLOGI WIRELESS AUTOMATIC NAHKODA) FOR SHIP - Setiawan, Hendra; Rachman, M Dieka; Yara, Galuh Diantie; Aprillisianti, Adelia; Amanda, Sophie (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
More than 60% or 3,257,483 km2 of Indonesia is covered by sea. Sea transportation is extremely important for economic integration and for domestic and international trade but unfortunately besides natural factor,Â  the biggest factor causing accident in the sea is human error. TEKWAN (Teknologi Wireless Automatic Nahkoda) for Ship is an autopilot system for ship and long distance controlled. TEKWAN for ship is a smart solution for Indonesiaâs sea problems, equipped with two cameras for computer vision and automatically avoid other ship or obstacle in shipâs track. There are some supporting systems such as GPS navigation, compass, radar systems, online systems and visualisation of digital maps which is connected to operator in TEKWAN.